Synthesis and characterisation of zirconium-modified neem seed for fluoride removal from aqueous media and groundwater - Aparna Singh; Srinivas Pasupuleti; Hari B. Vuthaluru; Gordon D. Ingram; Krishna Sandilya Durbha (Results in Chemistry, 2025)
Fluoride contamination of drinking water is a significant global problem that threatens human health. In this study, a novel adsorbent, denoted NS-Zr, was synthesised from neem seed, a plant waste material, that was modified by zirconium oxychloride octahydrate using ultrasound and carbonisation at 400, 600 and 800 °C. The adsorbent was characterised using FTIR, XRD, surface area, SEM-EDX, zero-point charge, and particle size analyses. Batch adsorption experiments with synthetic water investigated fluoride removal by altering contact time (5–180 min), adsorption temperature (30–60 °C), adsorbent dosage (0.1, 0.5, 1 g/100 mL), initial fluoride concentration (2–20 mg/L), and pH (alkaline to slightly acidic) for NS-Zr prepared at 600 and 800 °C. The adsorption data were well described by the Langmuir isotherm, were exothermic, and followed pseudo-first-order kinetics. The highest fluoride adsorption capacity of 1.36 mg/g and removal efficiency of 97.5 % were achieved with NS-Zr synthesised at 800 °C, with maximum removal occurring at pH 7. Additionally, NS-Zr was tested with groundwater samples from five locations collected both pre-monsoon and post-monsoon. Compared to synthetic water, performance with groundwater was reduced, with a maximum adsorption capacity of 0.17 mg/g and fluoride removal of 86 %. The adsorbents retained around 70 % of their initial fluoride removal capacity after three regeneration cycles. A proposed mechanism provides insight into the removal of fluoride by NS-Zr.